Export-import theory, practices, and procedures - Seyoum, Belay (Routledge, 2009)
References: p. 627 - 648; 7 sections (12 chapters): Overview of international trade; Export marketing and Strategy; Executing the transactions; Payment terms and procedures; Financing techniques and vehicles;...